Geographic Pattern of Bryophyte Species Richness in China: The Influence of Environment and Evolutionary History - Song, Xiaotong; Fang, Wenzhuo; Chi, Xiulian; Shao, Xiaoming; Wang, Qinggang (Frontiers in Ecology and Evolution, 2021)
How contemporary environment interacts with macroevolutionary processes to generate the geographic pattern of bryophyte species is still unresolved. China is very rich in bryophytes, with more than 3,000 bryophytes covering 70% of the families in the world. In this study, we assessed the effects of the contemporary environment (average temperature of the coldest season TCQ, precipitation of the warmest season PWQ, and elevational range) and the recent diversification rates (estimated as mean species number per genus, MSG) on the geographical pattern of species richness for bryophytes and two groups (i.e., liverworts and mosses) in China. We compiled the provincial level distribution of bryophyte species and estimated the geographic pattern of the recent diversification rate by MSG for species in China. Univariate, multivariate regressions and path model analyses were used to assess the relationships between species richness, MSG, and their potential environmental drivers. Species richness of all bryophytes and liverworts significantly increased with the increase of MSG, either in regressions or path analyses, indicating that provinces with high bryophyte richness were mainly inhabited by species (especially liverworts) from lineages with particularly high MSG. In contrast, the species richness of mosses was insignificantly decreased with MSG in univariate regression or insignificantly increased with MSG in path analysis. Both species richness and MSG of all bryophytes and liverworts increased with the increase in energy and water availability. In contrast, for mosses, the species richness significantly increased with the increase of energy and water availability, while MSG decreased with the increase of energy and water availability. The MSG of liverworts increase with the increase of elevational range but the MSG of mosses decrease with the increase of elevational range. Our study suggests that the humid tropical and subtropical mountains in China are not only diversity hotspots for bryophytes, but also cradles for high recent diversification of liverworts, and refuges for mosses to hold many monotypic and oligotypic genera.